Antibody response to inactivated influenza vaccine given by different routes in patients with chronic bronchopulmonary disease. Issue 6 (November 1973) - Shore, S. L.; Potter, C. W.; Stuart-Harris, C. H.
Abstract : Shore, S. L., Potter, C. W., and Stuart-Harris, C. H. (1973). Thorax, 28, 721-728. Antibody response to inactivated influenza vaccine given by different routes in patients with chronic bronchopulmonary disease. A comparison was made of the effects of administering inactivated bivalent influenza vaccine to 30 patients with chronic chest disease by various routes. The vaccine was given by subcutaneous injection to one group, by intranasal and intraoral spray on two successive days to a second group, and by both subcutaneous and intranasal routes to a third group of patients. Most of the patients suffered from chronic bronchitis with airways obstruction but three had asthma. The composition of the groups was adjusted in order that approximately the same number was present in each group of those with or without antibodies to influenza virus A2/Hong Kong/68. The titre of antibodies to this virus was measured in the serum and in sputum before and after immunization. The results were clearcut in that a greater proportion of those receiving subcutaneous vaccine with or without intranasal vaccine achieved a rise in HI antibodies and a higher titre of serum antibodies than those receiving vaccine purely by the respiratory route. Sputum antibodies were measured by both HI and tissue culture neutralization tests. The best sputum antibody responses were achieved by those receiving a single dose of subcutaneous vaccine. Those receiving vaccine by the respiratory route only achieved the poorest result and the third group immunized by both routes produced intermediate titres of sputum antibodies, thus suggesting an impairment of the local antibody response. These results are discussed with reference to the method of immunization against influenza of patients with chronic bronchitis.